2016
DOI: 10.21037/jss.2016.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Interspinous process spacers versus traditional decompression for lumbar spinal stenosis: systematic review and meta-analysis

Abstract: Current evidence indicates no superiority for mid- to long-term patient-reported outcomes for IPD compared with traditional bony decompression, with lesser surgical complications but at the risk of significantly higher reoperation rates and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
2
31
0
1
Order By: Relevance
“…Also, he concluded that the use of interspinous spacers did not appear to significantly change the clinical result of the surgery from that expected from decompression alone. Similar results are drawn from a metanalysis by Phan et al (11) finding no superiority for IPDs compared with traditional decompression, but higher reoperation rates and costs.…”
Section: Discussionsupporting
confidence: 81%
“…Also, he concluded that the use of interspinous spacers did not appear to significantly change the clinical result of the surgery from that expected from decompression alone. Similar results are drawn from a metanalysis by Phan et al (11) finding no superiority for IPDs compared with traditional decompression, but higher reoperation rates and costs.…”
Section: Discussionsupporting
confidence: 81%
“…Phan et al[ 17 ] included RCTs and prospective observational studies, limited to the English language. They found no superiority of IPDs compared to decompression and also found a higher reoperation rate in the IPD group.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials (RCT) have compared IPDs to conservative treatment [ 7 9 ] or to standard surgery[ 10 16 ], but there is an overall concern regarding bias risks and small population samples. Four systematic reviews have been published[ 17 20 ], but only one of these reviews examined exclusively RCTs[ 19 ]. Nevertheless, this systematic review included only 4 of the available studies.…”
Section: Introductionmentioning
confidence: 99%
“…The meta -analyses showed no significant difference on clinical outcomes in comparison with decompressive surgery. Additionally ISD has higher incidence of long -term reoperation and might lead to burden of cost [20,21]. Furthermore biomechanical changes such as decrease in ROM, and increase of interdiscal pressure and facet load at the adjacent segment following implantation of ISD are reported in both finite element and in vitro biomechanical studies [22,23].…”
Section: Discussionmentioning
confidence: 99%